Thrombosis in central obesity and metabolic syndrome: Mechanisms and epidemiology - Morange, Pierre-Emmanuel; Alessi, Marie-Christine (Thrombosis and Haemostasis, 2013)
Central obesity is a key feature of the metabolic syndrome (metS), a multiplex risk factor for subsequent development of type 2 diabetes and cardiovascular disease. Many metabolic alterations closely related to this condition exert effects on platelets and vascular cells. A procoagulant and hypofibrinolytic state has been identified, mainly underlain by inflammation, oxidative stress, dyslipidaemia, and ectopic fat that accompany central obesity. In support of these data, central obesity independently predisposes not only to atherothrombosis but also to venous thrombosis.
Keywords: Haemostasis; metabolic syndrome; visceral obesity; thrombosis